Peningkatan Gerak Dasar Manipulatif dalam Pembelajaran Pendidikan Jasmani Melalui Permainan Bola Berekor pada Anak Disabilitas Intelektual - Wildiana, Feby Putri; Yaum, Lailil Aflakul; Mais, Asrorul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to improve basic manipulative motor skills through the implementation of a ball game with a tail in children with intellectual disabilities at the PGRI Pamekasan Special Needs School (SLB). The study used Classroom Action Research (CAR) with two cycles, each consisting of planning, action, observation, and reflection. The study subjects included three ninth-grade students with moderate intellectual disabilities in the 2024/2025 academic year. Data collection techniques included observation, performance tests, and documentation, while data analysis used a descriptive qualitative approach with a calculation of the percentage of skill improvement. The results showed that the implementation of the ball game with a tail significantly improved students' throwing and catching abilities. The average manipulative skill score increased from 50% in the pre-cycle to 87.5% in the second cycle, with an average increase of 33.7%. Furthermore, there was an increase in students' motivation, courage, and active participation during the learning process. Thus, the ball game with a tail can be an effective alternative adaptive physical education method to improve basic motor skills in children with intellectual disabilities. Keywords: Intellectual Disabilities, Basic Manipulative Movement, Tailed Ball Game, Adaptive Physical Education